Multiscale anthropogenic impacts on stream condition and fish assemblages in Amazonian landscapes - Leal, Cecília Gontijo (2015)
Land use change and forest degradation are resulting in pervasive changes to tropical ecosystems around the globe, however consequences for freshwater ecosystems remain poorly understood. This is especially true for the Amazon basin, in particular for its complex network of low-order streams. These streams connect terrestrial and aquatic ecosystems throughout landscapes and host much, of the freshwater fish fauna of the Amazon basin. Despite the biological significance of these stream networks, the consequences of land use change for the condition of instream habitat and fish fauna remain very poorly studied and understood. This thesis aims to address part of this knowledge gap by investigating the effects of anthropogenic disturbances occurring at multiple spatial scales on stream condition and fish assemblages from human-modified Amazonian forests in the state of Pará, Brazil. The thesis starts by asking how instream habitat (composed of both water quality and physical habitat features) responds to landscape-scale anthropogenic disturbances and natural features (Chapter 2). Chapter 3 then investigates changes in fish species richness, abundance and composition following changes in both instream habitat and landscape-scale anthropogenic disturbance. Last, in Chapter 4 I attempt to disentangle the relative importance of those multiscale environmental predictor variables on species-specific disturbance responses, and evaluate the potential effectiveness of the Brazilian legislation in accounting for them. A total of 99 low-order streams were surveyed from five river basins in two large regions (Santarém and Paragominas) in the eastern Brazilian Amazon agricultural-forest frontier. I sampled a total of 25,526 fish specimens belonging to 143 species, 27 families and seven orders. Streams appeared to be exceptionally heterogeneous in their abiotic and biotic features. For instance the contribution of turnover to the beta stream site component was much higher than nestedness in all river basins. Overall these findings underscore the importance of multiple land use changes and disturbances, at multiple spatial scales, in shaping instream habitat, including links between catchment-scale forest cover and water temperature, and the impacts of road crossings on channel morphology. Both landscape and instream habitat variables were isolated as having a marked effect on stream fish, but instream habitat differences were shown to be particularly important in explaining patterns of fish species abundance compared to other landscape factors that are more amenable to management such as the protection of riparian forest strips. However the results of the thesis also highlight the complexity of Amazonian stream systems and the difficulties in disentangling the effects of multiscale environmental predictor variables underpinned by naturally heterogeneous biophysical characteristics – with instream habitat and fish assemblages affected by a broad suite of drivers that often varied across river basins and regions. I use the findings of the thesis to discuss challenges and recommendations for the management and conservation of low-order streams in Amazonian human-modified landscapes. In particular I emphasize the need for catchment-wide collective management approaches that go beyond the protection of riparian forests within individual properties as prioritized by existing Brazilian environmental legislation.